PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP HASIL BELAJAR SISWA KELAS VIII PADA MATA PELAJARAN FIQIH di MTs BAHRUL ULUM DESA AIR EMAS KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Ely Purnama Sari; Zulhaini Zulhaini; Alhairi Alhairi (Universitas Islam Kuantan Singingi, 2022)
The problem from this research started from the learning outcomes of class VIII1 students in fiqh subjects at MTs Bahrul Ulum, Air Emas Village, Singingi District, Kuantan Singingi Regency, which was still relatively low, as evidenced by the presence of students' scores below the KKM. This is the background for researchers to conduct research by distributing questionnaires related to the teacher's pedagogic competence and the questionnaires were filled out by class VIII1 students. Teacher pedagogic competence is the ability and skills of teachers in managing a learning process or teaching and learning interactions with students in the classroom. The purpose of this study was to determine the influence and factors that influence teacher pedagogic competence on student learning outcomes. The type of research used is quantitative research, the subject of this research is class VIII1 MTs Bahrul Ulum Air Emas Village, Singingi District, Kuantan Singingi Regency with a total of 20 students, data collection techniques used are observation, interviews, questionnaires and documentation. The results of the study indicate that there is an influence of teacher pedagogic competence on student learning outcomes, this is evident from the results of data analysis using SPSS. From the tests that have been carried out through simple linear regression analysis, the determination value of R2 is 0.101 X 100% = 10.1%. This shows that the influence of teacher pedagogic competence on learning outcomes is 10.1% while the remaining 80.9% is influenced by other variables.